HUBUNGAN TERPAAN SOCIAL MEDIA MARKETING DAN BRAND IMAGE DENGAN LOYALITAS KONSUMEN MARINA HAND AND BODY LOTION - Susi Santiaji; Joyo Nur Suryanto Gono; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Nowadays people are increasingly paying attention to body care. Based on consumer needs, the development of the body care business is growing rapidly, including hand and body lotion products. Marina carried out various strategies, namely social media marketing and instilling a positive image to compete with other brands as proven by Marina always being included in the Top Brand Award since 2015. In 2021, Marina experienced a decrease in consumer loyalty for hand and body lotion, while Marina's competitors experienced an increase in loyalty. This study aims to determine the relationship between exposure to social media marketing and brand image with consumer loyalty Marina hand and body lotion. This research is quantitative research with the type of explanatory research and using a non-probability sampling technique with a total of 100 respondents. The statistical test used is Kendall's Tau B. The theory used is Social Customer Relationship Management. The results of hypothesis testing using Kendall's Tau B test analysis show that exposure to social media marketing and consumer loyalty Marina hand and body lotion has a very significant relationship with a significance value of 0.003 <0.01 and a correlation coefficient of 0.273. Brand image variable has a very significant relationship with consumer loyalty Marina hand and body lotion with a significance value of 0.000 <0.01 and a correlation coefficient of 0.473.